Working Time and Role Strains of Research and Teaching Staff in a Modern Russian University - Roman Abramov; Ivan Gruzdev; Evgeniy Terentev (Voprosy obrazovaniya / Educational Studies Moscow, 2017)
The article touches upon the changes in roles within the academic profession in Russia arising from the education and science reform. The analysis is made through the example of the National Research University Higher School of Economics (HSE). Both quantitative and qualitative data is used to suggest a typology of faculties based on their work time allocation. The typology includes five types of faculties: teacher researchers, teachers, researchers, “universal soldiers”, and experts. Different types show different levels of  atisfaction with their work time budget: those who do a lot of teaching and administrative work tend to be less satisfied. This can be explained by the changes in the system of faculty certification in Russia and by how academic staff responds to those changes. Interview results are used to highlight the typical work time allocation problems faced by faculties. Those include a low degree of freedom to manage one’s own work time, the lack of boundary in work-life balance, excessive teaching load, an increase in unscheduled tasks, and the problem of workload delegation requiring high research and management skills.